Ultrasound viscoelastic imaging in differentiation of benign and malignant breast tumors - QIN Yu, LI Cheng, HUA Qing, ZHANG Huiting, JIA Wanru, DONG Yijie, ZHOU Jianqiao, XIA Shujun (Zhenduanxue lilun yu shijian)
Objective To evaluate the application value of ultrasonic viscoelastic imaging technology in differentia-ting benign and malignant breast tumors. Methods A total of 717 patients with breast tumors confirmed by surgical patho-logy were consecutively enrolled at Ruijin Hospital, Shanghai Jiao Tong University School of Medicine between February 2023 and August 2023, including 471 malignant and 246 benign cases. All patients underwent breast ultrasound examinations before treatment, including grayscale ultrasound, ultrasound strain elastography, ultrasound shear wave elastography, and ultrasound viscoelastic imaging. Ultrasound viscoelastic imaging technology included measuring four sets of parameters of the tumor and its surrounding tissues: viscosity coefficient, dispersion coefficient, shear wave elastic modulus, and strain ratio. Using the optimal predictive indicators from the four parameter groups, multiple prediction models were established, including single-variable models (viscosity coefficient, dispersion coefficient, shear wave, strain), a combined viscoelastic model (Shell/T-Vmean + Shell/T-Dmean), a Breast Imaging Reporting and Data System (BI-RADS) model, and a combined model integrating BI-RADS with viscoelastic parameters. The effectiveness of each model in differentiating benign and malignant breast tumors was evaluated. Results Parameters including viscosity coefficient, dispersion coefficient, elastic modulus, and strain ratio from ultrasound viscoelastic imaging could effectively distinguish benign and malignant breast tumors. Among them, the ratios of the tumor margin (2 mm region) to the tumor itself—Shell/T-Vmean, Shell/T-Dmean, Shell/T-Emean, and Strain Ratio A—were optimal predictive indicators, with areas under the curve (AUCs) of 0.742, 0.745, 0.726, and 0.705, respectively. The BI-RADS model for predicting benign and malignant breast tumors achieved an AUC of 0.822. When Shell/T-Vmean and Shell/T-Dmean were respectively combined with BI-RADS classification, the receiver operating characteristic (ROC) curve's AUC reached 0.895 (95% CI: 0.868–0.917), which was higher than that of BI-RADS alone. Conclusion Among the viscoelastic parameters of ultrasound viscoelastic imaging, the average ratios of viscosity coefficient, dispersion coefficient, and elastic modulus between the 2 mm tumor margin region and the tumor body are key diagnostic indicators. The combination of Shell/T-Vmean and Shell/T-Dmean with BI-RADS provides a new stra-tegy for noninvasive preoperative precision diagnosis.